2022
DOI: 10.1002/adfm.202112074
|View full text |Cite
|
Sign up to set email alerts
|

A Dual‐Functional Titanium Nitride Chloride Layered Matrix with Facile Lithium‐Ion Diffusion Path and Decoupled Electron Transport as High‐Capacity Anodes

Abstract: Intercalation typed electrodes are expected with low theoretical capacity, which falls behind their high rate performance and stability. In this work, α‐TiNCl, an isoelectronic system of TiO2, is designed as a promising high‐capacity intercalation anode. TiNCl features are layered TiN backbone terminated by Cl atoms. While the rocksalt TiN backbones function as electron conductors, the interlayer voids provide Cl‐coordinated Li+ sites without strong Li‐Ti repulsion, which proves to be a rapid diffusion path wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…It was observed that the peaks at 162.3 and 163.5 eV were related to S 2p 3/2 and S 2p 1/2 for S 2 2‑ , respectively. ,, Other peaks at 164.7 and 167.9 eV corresponded to C–S bonds and SO 4 2– , respectively. , Moreover, the intensity of the S 2p 3/2 peak for S 2 2– also decreased similar to Fe 2p 3/2 for Fe–S bonds, proving the existence of S vacancies. The high-resolution N 1s spectra of FeS 2 /C, V S -FeS 1.97 /C, V S -FeS 1.71 /C, and V S -FeS 1.65 /C nanorods in Figure e exhibited that there existed pyridinic-N and pyrrolic-N. , The high-resolution XPS spectra of C 1s for the FeS 2 /C, V S -FeS 1.97 /C, V S -FeS 1.71 /C, and V S -FeS 1.65 /C nanorods showed that two peaks at 284.6 and 285.9 eV were related to the C–C and C–S/C–N bonds (Figure f), respectively. …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…It was observed that the peaks at 162.3 and 163.5 eV were related to S 2p 3/2 and S 2p 1/2 for S 2 2‑ , respectively. ,, Other peaks at 164.7 and 167.9 eV corresponded to C–S bonds and SO 4 2– , respectively. , Moreover, the intensity of the S 2p 3/2 peak for S 2 2– also decreased similar to Fe 2p 3/2 for Fe–S bonds, proving the existence of S vacancies. The high-resolution N 1s spectra of FeS 2 /C, V S -FeS 1.97 /C, V S -FeS 1.71 /C, and V S -FeS 1.65 /C nanorods in Figure e exhibited that there existed pyridinic-N and pyrrolic-N. , The high-resolution XPS spectra of C 1s for the FeS 2 /C, V S -FeS 1.97 /C, V S -FeS 1.71 /C, and V S -FeS 1.65 /C nanorods showed that two peaks at 284.6 and 285.9 eV were related to the C–C and C–S/C–N bonds (Figure f), respectively. …”
Section: Resultsmentioning
confidence: 93%
“…40,41 Moreover, the intensity of the S 2p 3/2 peak for S 2 2− also decreased similar to Fe 2p 3/2 for Fe−S bonds, proving the existence of S vacancies. The highresolution N 1s spectra of FeS 2 /C, V S -FeS 1.97 /C, V S -FeS 1.71 /C, and V S -FeS 1.65 /C nanorods in Figure 3e exhibited that there existed pyridinic-N and pyrrolic-N. 7,42 The high-resolution XPS spectra of C 1s for the FeS 2 /C, V S -FeS 1.97 /C, V S -FeS 1.71 / C, and V S -FeS 1.65 /C nanorods showed that two peaks at 284.6 and 285.9 eV were related to the C−C and C−S/C−N bonds (Figure 3f), respectively. 43−45 To further affirm the presence and concentration of sulfur defects, EPR and ICP-OES were carried out.…”
Section: Morphological and Structural Characterizationsmentioning
confidence: 95%
See 1 more Smart Citation
“…47 The diffusion coefficient D ions can be calculated by the following eqn (1): 48 where τ represents the diffusion time, L is the diffusion length, Δ E s corresponds to the steady-state voltage change through a single-step GITT test, and Δ E τ is derived from the total change in the cell voltage to eliminate the iR drop during the constant current pulse τ of the GITT. 49,50…”
Section: Influence Factors Of High-rate Performancementioning
confidence: 99%
“…where s represents the diffusion time, L is the diffusion length, DE s corresponds to the steady-state voltage change through a single-step GITT test, and DE s is derived from the total change in the cell voltage to eliminate the iR drop during the constant current pulse s of the GITT. 49,50 The diffusion time s and diffusion length L are related via the following formula (2):…”
Section: Diffusionmentioning
confidence: 99%